The role of Asset Management, Cost Control, and receivables management policies in improving the Financial Resilience of PT Unilever - Rulis Setyowati; Vivi Ade Rivani; Yunita Budi A M; Maria Yovita R. Pandin (Pusat Riset dan Inovasi Nasional, 2023)
This article discusses the role of asset management, cost control, and receivables management policies in improving financial resilience amid the Covid-19 outbreak, PT Unilever. The COVID-19 epidemic put tremendous financial pressure on many businesses, including Unilever. The research of this article was conducted using ku research methodologyantitaif.The result of thi re earchmviewAsset Management, Cost Control, and receivables policies have significant potential for Unilever'S long-term financial stability. Effective management of an organization's assets helps improve the efficiency and effectiveness of the use of those assets, enabling the organization to maximize the potential financial benefits of those assets. Effective monetary management can reduce the company's operating costs and increase profitability. A good receivables policy can also help reduce credit risk and improve business license requirements. In conclusion, this article highlights how important it is to use asset management, cost control, and receivables policies to improve a company's financial performance, especially in difficult situations such as the COVID-19 pandemic.